2011
DOI: 10.1103/physrevb.84.024521
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen in layered iron arsenides: Indirect electron doping to induce superconductivity

Abstract: Utilizing the high stability of calcium and rare earth hydrides, CaFeAsF 1−x H x (x = 0.0-1.0) and SmFeAsO 1−x H x (x = 0.0-0.47) have been first synthesized using high pressure to form hydrogen-substituted 1111 type iron-arsenide superconductors. Neutron diffraction and density functional calculations have demonstrated that the hydrogens are incorporated as H − ions occupying F − sites in the blocking layer of CaFeAsF. The resulting CaFeAsF 1−x H x is non-superconducting, whereas SmFeAsO 1−x H x is a supercon… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
167
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 118 publications
(178 citation statements)
references
References 56 publications
11
167
0
Order By: Relevance
“…As reported previously, LaFeAsO 1 − x H x was synthesized by solid-state reactions using starting materials La 2 O 3 , LaAs, LaH 2 , FeAs and Fe 2 As under high pressure 11 . The phase purity and structural parameters at room temperature were determined by powder X-ray diffraction measurements with MoKα1 radiation.…”
Section: Methodsmentioning
confidence: 94%
“…As reported previously, LaFeAsO 1 − x H x was synthesized by solid-state reactions using starting materials La 2 O 3 , LaAs, LaH 2 , FeAs and Fe 2 As under high pressure 11 . The phase purity and structural parameters at room temperature were determined by powder X-ray diffraction measurements with MoKα1 radiation.…”
Section: Methodsmentioning
confidence: 94%
“…The rare earth (RE)FeAsO phases are AFM metals at low temperature. The electron doping via hydride ion substitution into the oxygen site results in the suppression of AFM (AFM1) ordering and subsequently the emergence of a superconducting phase for the electron doping range of 0.05 ≤ e − /Fe ≤ 0.45 (11,12). The optimum T c , which depends strikingly on the RE size, is 36 K for RE = La, and 56 K for Sm or Gd, consistent with the observation that the application of physical pressure to La-1111 can enhance its T c from 36 K to 52 K (12,13).…”
mentioning
confidence: 99%
“…A similar finding has been reported for undoped Ba/Sr122 single crystals, 86,87) in which the strain generated during crystal growth induces the superconductivity. Subsequently, it was reported that water-related species induce superconductivity in bulk samples of 1111 88,89) and 11 compounds [90][91][92] (as discussed later, there have been a few reports on 11 thin films). Thus, elucidating the interaction of water-related chemical species with the parent compounds could provide insight into the superconducting mechanism or a clue to realizing a higher T c by new doping methods such as chemical modification.…”
Section: Sr Systemmentioning
confidence: 96%
“…Note that Hanna et al 89) recently reported that hydrogen can be incorporated as H À anions and occupy the O 2À sites in the 1111 phase. The resulting SmFeAsO 1Àx H x (x ' 0:2) is a superconductor with T onset c ' 55 K. Additionally, up to 40% of the O 2À ions can be replaced by H À anions, along with electrons being supplied into the FeAs layer to maintain the charge neutrality (…”
Section: Sr Systemmentioning
confidence: 99%